Differential Subordination Defined by New Generalised Derivative Operator for Analytic Functions - Ma'moun Harayzeh Al-Abbadi; Maslina Darus (International Journal of Mathematics and Mathematical Sciences)
A new generalised derivative operator μλ1,λ2n,m is introduced. This operator generalised many well-known operators studied earlier by many authors. Using the technique of differential subordination, we will study some of the properties of differential subordination. In addition we investigate several interesting properties of the new generalised derivative operator.